Impact of climate change on health in Afghanistan amidst a humanitarian crisis - Waniyah Masood; Sakina Aquil; Hamid ullah; Arsalan Nadeem; Hassan Mehmood; Zarmina Islam; Mohammad Yasir Essar; Shoaib Ahmad (Elsevier, 2022)
Climate change is considered an important factor contributing to increased mortality and morbidity. Particularly, climate change in Kabul, Afghanistan has affected the health of millions of people by increasing their susceptibility to infectious diseases, respiratory problems, and other health conditions. Prompt climate preservation and health-related interventions could be a community-wide approach to improve the current conditions. In this review paper, we highlight the health implications associated with climate change in Afghanistan and discuss preventive measures to tackle the climate-associated adverse health conditions in the future.